Antimicrobial Resistance and Wildlife: Occurrence of Antimicrobial Resistance Genes in Red Foxes (Vulpes vulpes, Linnaeus, 1758), in Italy - Antonietta Di Francesco; Daniela Salvatore; Roberta Taddei; Fabrizio Bertelloni; Caterina Lupini; Giulia Cagnoli; Valentina Virginia Ebani (Animals, 2025)
Clinically significant antimicrobial-resistant bacteria and resistance genes are increasingly being reported in wildlife. In this study, 127 splenic samples from red foxes (Vulpes vulpes) from northern and central Italy were analysed for the presence of resistance genes against antimicrobials such as tetracycline, sulphonamide, β-lactam, and colistin, which were previously extensively used in human and veterinary management of bacterial diseases. One or more antimicrobial resistance genes were detected in 78 (61%) of 127 splenic samples. Polymerase chain reaction positivity was revealed for 13 genes—tet(A), tet(B), tet(K), tet(L), tet(M), tet(O), tetA(P), tet(Q), tet(S), tet(X), sul1, sul2, and blaTEM-1—out of the 21 tested genes. Our results, corroborated by reports in the literature, confirm the potential role of the red fox as a sentinel for antimicrobial-resistant bacteria in contaminated environments and suggest that detecting resistance genes in biological samples by a culture-independent method might be an effective tool for the epidemiological study of antimicrobial resistance in wildlife.